PEREMAJAAN KOTA UNTUK PERMUKIMAN KUMUH DI PERKOTAAN: ANTARA STRATEGI DAN SOLUSI - Oot Hotimah (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2013)
Improvement of social welfare is the responsibility of the government. One way to overcome poverty and improve the poor quality of the living environment of the urban poor is a more humane manner by involving them in development planning. The conventional approach in the form of eviction for urban renewal undertaken during this creates urban social problems more acute and complicated and not sustainable in overcoming poverty. One of the policies that need to be taken, among others, is to build low-rent flats and community involvement in public policy making. The advantage is the increased sense of community and they can become agents of development control.